Effects of Nitrogen Fertilization and Soil Inoculation of Sulfur-Oxidizing or Nitrogen-Fixing Bacteria on Onion Plant Growth and Yield - Nemat M. Awad; A. A. Abd El-Kader; M. Attia; A. K. Alva (International Journal of Agronomy)
A field experiment was conducted in a newly reclaimed soil at El-Saff region, El-Giza Governorate, Egypt to study the effects of different rates of nitrogen (N: 62 to 248 kg ha-1) with or without soil inoculation of sulfur- (S-) oxidizing bacteria (SoxB) and combined inoculation of SoxB and N-fixing bacteria (NFxB) on yield, quality and nutritional status of onion (Allium cepa L., “Giza 20”). Elemental S at 620 kg ha-1 was applied to all treatments. Application of N at 62, 124, and 248 kg ha-1 rates increased onion yield, plant height, and N uptake by 28 to 76%, 32 to 53%, and 61 to 145%, as compared to those of the plants that received no N. Inoculation of SoxB at various N rates increased onion yields by 47 to 69% and N uptake by 76 to 93%, as compared to those of the plants which received the respective rates of N but no SoxB inoculation. Inoculation with SoxB and NFxB increased onion yield by 221%, plant height by 62%, and N uptake by 629%, as compared to those of the plants grown without inoculation and no N applied.